EVIDENCE BASED CASE REPORT (EBCR): PENGARUH MENYUSUI SELAMA IMUNISASI TERHADAP NYERI PADA NENONATUS CUKUP BULAN (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Immunization as a form of effective preventive program to reduce mortality in infants and toddlers. Pain is one of the side effects of giving immunization by injection which can cause distress in the baby. Experiences of pain that are not treated immediately can have a long-term physiological as well as psychological impact on the child. Feeding method as a safe and effective method of relieving pain in newborns. Breastfeeding during immunization can be one of the nonpharmacological alternatives because this intervention is costless and easy to implement because it does not require other additional equipment. Purpose: The purpose of evidence-based use of this breastfeeding method is to reduce or minimize pain during immunization. Method: The method used is by tracing evidence through databases from Pubmed and Cochrane with the publication year 2012-2022. Result: The result of differences in pain levels measured by the AND scale between neonates who were given breastfeeding interventions during immunization was 4 and those who were not given interventions were 7. Conclusion: Breastfeeding reduces pain during immunization injections.